2017
DOI: 10.1186/s12199-017-0639-2
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa, depression and suicidal thoughts among Chinese adolescents: a national school-based cross-sectional study

Abstract: BackgroundAlthough there is much literature on adolescent suicide, combined effects of depression and anorexia nervosa on suicide were rarely investigated. The aims of this study are to examine the association between anorexia nervosa and suicidal thoughts and explore the interaction between anorexia nervosa and depression.MethodsThis is a cross-sectional study, in the study, a sample of 8,746 Chinese adolescents was selected by multistage stratified method in 2012/2013 from 20 middle schools in 7 provinces ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
3
15
0
5
Order By: Relevance
“…In adolescence, especially in females, being taunted about being overweight or obese may contribute to the development of eating disorders such as anorexia nervosa, and internalizing problems such as suicidal thoughts and depression ( Lian et al, 2017 ). Significant residual obesity stigma remains against individuals who have lost weight ( Latner, Ebneter & O’Brien, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In adolescence, especially in females, being taunted about being overweight or obese may contribute to the development of eating disorders such as anorexia nervosa, and internalizing problems such as suicidal thoughts and depression ( Lian et al, 2017 ). Significant residual obesity stigma remains against individuals who have lost weight ( Latner, Ebneter & O’Brien, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent studies on bulimic behaviours were conducted on the population of Brazilian women and were published by de Carvalho et al [28]. This topic has also been mentioned in research by Chapuis-de-Andrade et al [40]. In the first of these studies, the authors examined a sample of 27,501 volunteers aged 18-55, whose average age was 28.9 ± 8.7 years.…”
Section: Similarities and Differences Between Polish And Japanese Womenmentioning
confidence: 99%
“…In addition to physical (e.g., BMI-Body Mass Index) and socio-cultural risk factors, the psychological factors supporting the development of unhealthy eating behaviours are also worth mentioning. People who suffer from eating disorders often present comorbid disorders such as anxiety and affective disorders, self-harm, or abuse of psychoactive substances [4,40]. Chapuis-de-Andrade et al [36] studied a population of Brazilians with an average age of 28.9 ± 8.7 years (women constituted 69% of the research group): The results showed significant correlations between compensatory (bulimic) eating behaviours and affective factors.…”
Section: Risk Factors For Eating Disordersmentioning
confidence: 99%
“…These girls were sampled using the multistage cluster sampling strategy. 14 There were 24 girls with missing records regarding menarche and 788 girls refused to undergo the physical examination (online supplementary table S ). Finally, 3478 girls were interviewed by both CASI and FFI.…”
Section: Methodsmentioning
confidence: 99%